Selection of a simulation language for an MBA modeling and simulation course - Archer, Norman P.; McMaster University, Faculty of Business (My University, 1984)
A study was carried out with two student sections of an MBA modeling and simulation course, to examine the feasibility of switching to a different simulation language from the one currently used. Data collected during the study also indicated the value of a project-oriented approach in the course, and indicated that more emphasis could be placed on learning the simulation language by self-teaching, leaving more class time for learning other aspects of simulation.
18, 8 p. ; Includes bibliographical references (p. 11-12) ; "June, 1984".
Keywords: Education; Systems; Simulation; Business > Mathematical models Business > Computer simulation GPSS (Computer program language) Business education > Simulation methods Business education > Ontario > Hamilton Programming languages (Electronic computers) > Study and teaching (Graduate)